Argumentation real-world inquiry to improve students' argumentation skill - Rita Istiana; Desti Herawati; Didit Ardianto (JURNAL BIOEDUKATIKA, 2020)
Student teachers poor argumentation skill is one of the problems that should be solved. This research aims to develop an Argumentation Real-World Inquiry learning model that incorporates argumentation session on environmental, socio-scientific issues at each stage. The research subjects were the biology student teachers taking the Environmental Knowledge course. The research method used was Research and Development (R&D) which comprised 3 stages: Phase 1 (Development), Phase II (Pre-Experiment), and Phase III (Implementation and Evaluation). The data on argumentation skill were obtained from an essay that addressed the environmental, sociocultural issue about environmental pollution. The pre-experiment phase was conducted using weak experiment method and one group pretest-posttest design, while in the implementation phase, quasi experiment method and pretest-posttest control group design were used. The results of the pre-experiment stage showed that the learning model was able to increase the student teachers' argumentation skill, indicated by an increase in level 3 argumentation from 16% (pretest) to 68% (posttest) and a decrease in level 2 argumentation from 74% (pretest) to 21 % (posttest). The results of the implementation phase showed that the student teachers' argumentation skill improved, with N-Gain score of 0.307 (medium category). The results of this research indicate that the Argumentation Real-World Inquiry learning model is able to train student teachers to develop their argumentation skill on environmental, socio-scientific issues.